Breastmilk cell trafficking induces microchimerism‐mediated immune system maturation in the infant. Issue 2 (8th January 2018) - Molès, Jean‐Pierre; Tuaillon, Edouard; Kankasa, Chipepo; Bedin, Anne‐Sophie; Nagot, Nicolas; Marchant, Arnaud; McDermid, Joann M.; Van de Perre, Philippe
Abstract: Initiating breastfeeding within the first hour of life confers an important benefit in terms of child mortality and severe morbidity. Intestinal permeability to ingested macromolecules and immunoglobulins is limited to the first days of human life. These exchanges cease in the very early post‐partum period but may increase beyond the neonatal period in response to local inflammation or introduction of a weaning food. From animal‐ and limited human‐based observations, compelling evidence points out to breastmilk cells also trafficking from mother to infant mucosal tissues and participating to the maternal microchimerism. The precise nature of breastmilk cells that are involved is presently not known but likely includes progenitor/stem cells—representing up to 6% of breastmilk cells—with possible contribution of mature immune cells. Stem cell microchimerism may induce tolerance to non‐inherited maternal antigens (NIMAs), breastfeeding generating regulatory T cells (Treg ) that suppress antimaternal immunity. Therefore, in complement to pregnancy‐induced microchimerism, breastfeeding‐induced microchimerism may be pivotal in infant immune development, intestinal tissue repair/growth and protection against infectious diseases. As a continuum of the gestational period, the neonatal gut may be considered as a temporary, but important developmental extension of the role played by the placenta during intrauterine life; breastmilk playing the role of maternal blood by delivering maternal soluble factors (macromolecules, Ig, cytokines) and immunologically active milk cells. A better understanding of breastfeeding‐induced maternal microchimerism would provide further evidence in support of public health messages that reinforce the importance of early initiation of breastfeeding. Abstract :